Предмет: Алгебра,
автор: Sabohat2001
a/(x+1)+(bx+c)/(x^2-x+1)=1/(x^3+1)
Ответы
Автор ответа:
0
A/(x+1)+(bx+c)/(x²-x+1)=1/(x+1)(x²-x+1)
x≠-1
A(x²-x+1)+(bx+c)(x+1)=1
Ax²-Ax+A+bx²+bx+cx+c=1
x²(A+b)+x(b+c-A)+(A+c)=1
{A+b=0⇒A=-b
{b+c-A=0⇒2b+c=0⇒c=-2b
{A+c=1⇒-b-2b=1⇒-3b=1⇒b=-1/3
A=1/3
c=2/3
x≠-1
A(x²-x+1)+(bx+c)(x+1)=1
Ax²-Ax+A+bx²+bx+cx+c=1
x²(A+b)+x(b+c-A)+(A+c)=1
{A+b=0⇒A=-b
{b+c-A=0⇒2b+c=0⇒c=-2b
{A+c=1⇒-b-2b=1⇒-3b=1⇒b=-1/3
A=1/3
c=2/3
Автор ответа:
0
Спасибо!!!!:):):)Thanks!!!
Похожие вопросы
Предмет: Химия,
автор: leraaaa01
Предмет: Литература,
автор: aishasaparbekkyzy
Предмет: Физика,
автор: vyakush18
Предмет: Экономика,
автор: MrsClifford
Предмет: История,
автор: Аноним